2016
DOI: 10.1016/j.sleep.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective and risk factors associated with adolescent sleep: findings from Australia, Canada, and The Netherlands

Abstract: Results indicate that when designing interventions for adolescent sleep, multiple lifestyle factors need to be considered, whereas country of residence may play a lesser role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 51 publications
6
32
0
6
Order By: Relevance
“…naps and caffeine consumption), it does not include any questions pertaining to technology use in the bed. As adolescents are a population with a high affinity for technology use around bedtime (Bartel et al, ), our findings have implications for examining SEL in this vulnerable group. Thus, in light of the present study's findings, current self‐report measures of sleep may require modification, both regarding the timing of SEL and the activities engaged in during SEL.…”
Section: Discussionmentioning
confidence: 80%
“…naps and caffeine consumption), it does not include any questions pertaining to technology use in the bed. As adolescents are a population with a high affinity for technology use around bedtime (Bartel et al, ), our findings have implications for examining SEL in this vulnerable group. Thus, in light of the present study's findings, current self‐report measures of sleep may require modification, both regarding the timing of SEL and the activities engaged in during SEL.…”
Section: Discussionmentioning
confidence: 80%
“…Overall, 19 analyses were conducted that investigated the role of household chaos on health and health behaviours: (1) 9 papers specifically looked at physical health outcomes, disease, and communication disorder outcomes (13,83,102,109,(114)(115)(116)(117)(118), including glycaemic control, child health, weight status, and stutter, (2) 3 studies investigated diet and dietary behaviours (102,119,120), (3) 6 studies looked at sleep (14,53,97,106,121,122), and (4) 2 studies assessed other outcomes, including TV viewing behaviours in a laboratory setting (123) and mothers' perceptions on children's physical activity (124). For glycaemic control, both maternal and paternal household chaos scores were positively associated with HbA1c in children and adolescents with type 1 diabetes (114) and in children aged 1-13 years with type 1 diabetes mellitus (116).…”
Section: Physical Health Health Behaviours and Communication Disordersmentioning
confidence: 99%
“…With respect to sleep, a more chaotic home environment was associated with mixed effects on sleep outcomes in adolescents, including sleep onset latency and sleep duration (121,122); however, in younger children greater scores for household chaos were significantly associated with higher parent-reported scores for bedtime resistance, sleep anxiety, and total sleep problems (14). One study found that infants from highly chaotic homes demonstrated delays in sleep consolidation patterns and greater fragmentation of sleep; however, they also reported longer and more variable sleep duration compared with infants in low chaos homes (106).…”
Section: Physical Health Health Behaviours and Communication Disordersmentioning
confidence: 99%
“…Additionally, requesting adolescents set a reminder may improve regular activity completion. Due to the association between pre‐sleep arousal and SOL in non‐sleep‐disordered adolescents (Bartel et al., ), this study aimed to determine the effects of low‐intensity interventions on SOL and pre‐sleep cognitive arousal broadly (i.e. in schools).…”
Section: Discussionmentioning
confidence: 99%